A biomechanical analysis of a "boost" in synchronised swimming - Kubo, Y.; Homma, Mi.; Homma, Ma.; Takamatsu, J.; Ito, K.; Ichikawa, H. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION The height of each body segment above the water surface during a routine is one of the most important factors to get higher score in a synchronised swimming. Although an element "boost" is required powerful and well-coordinated movement to raise the whole body highly, few studies have been done about the details of this movement from views of above the water surface and underwater. The purposes of this study were to compare the boost motion of the swimmers participated in the 9th FINA World Championships 2001 and to investigate the techniques, which could carry out higher boost. METHODS The height of each body segment above the water surface was calculated from the distances of the swimmers to a DV camera (60fps) set at the pool deck and the coefficients for the calibration of the longitudinal errors. The distances of the swimmers to a camera were calculated by a two-dimensional DLT method and the coefficients for the calibration of the longitudinal errors were calculated from the length of several control poles set up the water surface level. Additionally, a three-dimensional DLT method with two underwater cameras (60fps) was used for a motion analysis of underwater legs. RESULTS There were two types of the boost motion above the water surface (Figure1). One type raised the head highly and kept the height of it, but the peak height of the hand was low (keep head type). Another type raised the hand highly and kept the height of it, but the peak height of the head was low (keep hand type). A swimmer of the keep head type showed two kicks like a breaststroke (whip flips) in the raising phase and in the falling phase, respectively. On the other hand, a keep hand type swimmer showed one whip flips in the raising phase and showed the kicks like a screw (egg beater) in the falling phase. Because a keep head type swimmer was required the greater force than a keep hand type swimmer to keep the height of the trunk and the head that have large mass, she showed the whip flips that could generate greater force in the falling phase.